Alemtuzumab for the treatment of multiple sclerosis - Willis MD; Robertson NP (Dove Medical Press, 2015)
Mark D Willis, Neil P Robertson Institute of Psychological Medicine and Clinical Neuroscience, Cardiff University, University Hospital of Wales, Heath Park, Cardiff, UK Abstract: Alemtuzumab is an anti-CD52 monoclonal antibody, recently approved for the treatment of active, relapsing multiple sclerosis (MS). Administration of alemtuzumab causes a rapid and dramatic reduction in circulating lymphocytes, with a predictable subsequent pattern of immune reconstitution. Although the precise mode of action remains unclear, treatment results in a marked reduction in annualized relapse rates, slowing of disability progression compared with an active comparator, and may even cause disability reversal. Although conferring clear clinical benefits, alemtuzumab carries a significant long-term risk of autoimmune disease (AID), which has a particular predilection for the thyroid gland, although a wide range of other disorders have also been reported. However, risks of AID can usually be anticipated and treated successfully, provided rigorous monitoring and surveillance protocols are followed by clinicians and patients alike. Despite its immunosuppressive mechanism of action serious infections are rare and malignancies commonly associated with immunodeficiency have not been observed to date. Alemtuzumab’s unique mode of administration, as well as it’s durability of effect, provides an important addition to currently available therapeutic interventions for MS, and in particular is a valuable treatment option in recent onset and highly active relapsing disease. Keywords: multiple sclerosis, alemtuzumab, autoimmune disease